AN INTERPRETER-BASED TWO-USER DATA MANAGEMENT SYSTEM FOR A SMALL MINICOMPUTER / UN SYSTEME D’ADMINISTRATION "INTERPRETER BASED TWO-USER" DE DONNEES POUR UN PETIT MINICOMPUTER - Covey, H. D.; Boughner, S. G.; Wigle, E. D. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see PDF